Secure OpenID Authentication Model by Using Trusted Computing - E. Ghazizadeh; Z. S. Shams Dolatabadi; R. Khaleghparast; M. Zamani; A. A. Manaf; M. S. Abdullah (Abstract and Applied Analysis)
The growth of Internet online services has been very quick in recent years. Each online service requires Internet users to create a new account to use the service. The problem can be seen when each user usually needs more than one service and, consequently, has numerous accounts. These numerous accounts have to be managed in a secure and simple way to be protected against identity theft. Single sign-on (SSO) and OpenID have been used to decrease the complexity of managing numerous accounts required in the Internet identity environment. Trusted Platform Module (TPM) and Trust Multitenancy are great trusted computing-based technologies to solve security concerns in the Internet identity environment. Since trust is one of the pillars of security in the cloud, this paper analyzes the existing cloud identity techniques in order to investigate their strengths and weaknesses. This paper proposes a model in which One Time Password (OTP), TPM, and OpenID are used to provide a solution against phishing as a common identity theft in cloud environment.